Diseño de instalación de una planta para purificación de glicerina obtenida en la producción de biodiesel - Ruíz Barahona, Eduardo Manuel (2013)
The problem of fossil fuels today is closely linked to contamination by gases generated by its use; due to this, there are new alternative fuels. The biodiesel is presented as an alternative for replacing fossil fuels, because of its high viscosity lengthens the life of the engine and its composition is less than the degree of contamination to the environment. In the production process of biodiesel by products are generated, one of them and the most important is glycerin. Therefore we present an alternative for the processing of crude glycerin, through thermal heating operations, ion exchange and evaporation to obtain glycerol with purity acceptable and thus give added value to its production and its use as an input in the pharmaceutical, cosmetic, explosive, food products, etc. This is the reason whereby in this study is intended for installation design a purification plant glycerin obtained from biodiesel, in which was performed market research, equipment design, environmental impact analysis and economic evaluation. The project concludes that it is economically viable, since it represents an added value to the production of biodiesel